2018
DOI: 10.5194/angeo-36-139-2018
|View full text |Cite
|
Sign up to set email alerts
|

Latitude-dependent delay in the responses of the equatorial electrojet and <i>S</i><sub><i>q</i></sub> currents to X-class solar flares

Abstract: Abstract. We have analyzed low-latitude ionospheric current responses to two intense (X-class) solar flares that occurred on 13 May 2013 and 11 March 2015. Sudden intensifications, in response to solar flare radiation impulses, in the S q and equatorial electrojet (EEJ) currents, as detected by magnetometers over equatorial and low-latitude sites in South America, are studied. In particular we show for the first time that a 5 to 8 min time delay is present in the peak effect in the EEJ, with respect that of S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The equatorial ionosphere is disturbed significantly during space weather events, including the solar flares and geomagnetic storms. When a solar flare erupts, the sudden enhancement in solar radiation increases the ionization in the E region and modifies the ionospheric electrodynamics (e.g., H. Liu et al, ; Nogueira et al, ; Xiong et al, ; Zhang, Liu, Le, & Chen, ). Solar flares often cause an impulsive increase in the dayside eastward EEJ (e.g., Manju et al, ; Rastogi et al, ; Xiong et al, ; Zhang, Liu, Le, & Chen, ) and also produce a westward increase under a counter electrojet condition (e.g., Rastogi et al, , ; Sripathi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The equatorial ionosphere is disturbed significantly during space weather events, including the solar flares and geomagnetic storms. When a solar flare erupts, the sudden enhancement in solar radiation increases the ionization in the E region and modifies the ionospheric electrodynamics (e.g., H. Liu et al, ; Nogueira et al, ; Xiong et al, ; Zhang, Liu, Le, & Chen, ). Solar flares often cause an impulsive increase in the dayside eastward EEJ (e.g., Manju et al, ; Rastogi et al, ; Xiong et al, ; Zhang, Liu, Le, & Chen, ) and also produce a westward increase under a counter electrojet condition (e.g., Rastogi et al, , ; Sripathi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…(2018), an equivalent current system of the geomagnetic crochets (SFE) during the 24 September 2011 flare event had a pattern similar to the background Sq current system at low and mid‐latitudes, and positive crochet was seen in the magnetometer measurements. However since the EEJ currents are weaker during the winter solstice period (Yamazaki & Maute, 2017, references there in), we can anticipate that any modifications in the conductivity can further modulate the electric field and hence the EEJ intensity (Nogueira et al., 2018; Qian et al., 2012; Richmond, 1973; Zhang et al., 2017). In fact, it has already been shown that compared to equinox and summer solstice, the magnitude of crochet is always small during the winter solstice period (Chakrabarty et al., 2013; Manju & Viswanathan, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Equation ). There are studies reporting variations in the Ex during solar flare events (Nogueira et al., 2018; Qian et al., 2012; Zhang et al., 2017). Any change in the conductivity or Ex can influence Ez as well.…”
Section: Model Simulations By Quasi‐two Dimensional Photochemical Modelmentioning
confidence: 99%